Compliance of abstracts of randomized control trials with CONSORT guidelines: A case study of Balkan journals - Necdet Sut; Zafer Koçak; Selcuk Korkmaz; Cem Uzun (European Science Editing, 2022)
Background: Published reports of randomized controlled trials (RCTs) are not compliant with the CONSORT checklist as much as they should.Objective: To assess the quality, in terms of the level to which they are compliant with the CONSORT checklist, of abstracts of RCTs published in general medical journals in the Balkan region.Methods: Two observers assessed the abstracts of RCTs published in five general medical journals of the Balkan region between 2012 and 2018 to determine the level to which the abstracts were compliant with the 16-item CONSORT abstracts checklist.Results: Of the 183 studies that were identified for evaluation, 124 (67.8%) were excluded from the evaluation. The average compliance level was 44.5% (95% CI: 41.9%–47.1%), the lowest being that for randomization (1.7%), funding (1.7%),numbers analysed (11.0%), blinding (13.6%), and trial registration (18.6%). However, the compliance level was very high for conclusions (99.2%), objectives (96.6%), interventions (95.8%), and primary outcomes (83.9%). The length of the abstract (word count) and the level of compliance were positively correlated (rs = 0.43; p = 0.001). Abstracts of trials published in journals that endorse CONSORT in their publication policies were more compliant than those published in other journals (47.5 ± 10.4 versus 40.8 ± 8.0, p = 0.024).Conclusion: The overall level of compliance with the CONSORT checklist was below 50%. To improve the quality of abstracts of RCTs, authors should be encouraged to use the CONSORT checklist, and editors should check compliance with the CONSORT guidelines as part the publishing workflow.